MO067DELETION AND BLOCKAGE OF KININ B1 RECEPTOR EXACERBATES CISPLATIN-INDUCED CKD. (29th May 2021) - Estrela, Gabriel; Budu, Alexandre; Freitas-Lima, Leandro; Arruda, Adriano; Perilhão, Mauro; Barrera-Chimal, Jonatan; Araujo, Ronaldo
Abstract: Background and Aims: Kinins plays a major role in immune response, where kinin B2 receptor is constitutively expressed and kinin B1 receptor is induced under inflammatory stimuli. Kinin B1 receptor deletion and blockage has been shown to have beneficial effects in some models of renal diseases. Multiple acute renal insults, even if followed by renal recovery, is a risk factor for the future development of chronic kidney disease (CKD) and end-stage renal disease (ESRD). Our main objective was to determine the importance of kinin B1 receptor in tubulointerstitial fibrosis induced by ongoing cisplatin treatment. Method: Male C57/Bl6 mice were divided in 3 groups, vehicle, cisplatin, cisplatin + R715 (kinin B1 receptor antagonist). Animals has been treated with multiple doses of cisplatin (7mg/kg i.p) once a week during 4 weeks and R715 (0.8mg/kg i.p) 48, 24 and 1 hour prior to cisplatin injections. We also used B1KO mice (C57Bl6 background) and WT mice (littermates). Mice were euthanized after 30 days of last cisplatin injection. Renal parameters, histology, real time PCR were performed to investigate renal injury, inflammation and fibrosis. Results: Cisplatin treatment increases most of renal parameters, renal injury and fibrosis markers. Deletion of B1 receptor exacerbates significantly creatinine (WT CIS 0, 60+ 0, 03 B1KO 0, 76+ 0, 01 mg/dL), urea (WT CIS 111, 8+ 5, 638 B1KO CIS 240, 8+ 28, 60 mg/dL), and protein excretion (WT CIS 0, 0058+ 0, 0011 B1KO CIS 0, 0121+ 0, 0007 mg/24h). Association of cisplatin with R715 increased creatinine levels (veh 0, 43+ 0, 03 cis+R715 0, 64+ 0, 04 mg/dL), exacerbates urea (cis 95, 51 + 3, 926 cis+ R715 158, 9+ 14, 40 mg/dL) and protein excretion (cis 0, 012+ 0, 002 cis+R715 0, 018+ 0, 003 mg/24h). Renal injury markers such as KIM-1 and TNF-a showed no significant differences. NGAL expression exacerbates (cis 2, 53+ 0, 44 cis+R715 5, 66+ 1, 34) and tubular injury score (cis 0, 130+ 0, 021 cis+R715 0, 191+ 0, 020) is higher in cisplatin+R715 group. Fibrosis markers a-SMA (cis 2, 56+ 0, 43 cis+R715 4, 67+ 0, 99), Col4 (cis 2, 57+ 0, 39 cis+R715 5, 14+ 1, 01) and Vimentin (2, 69+ 0, 31 cis+R715 4, 62+ 0, 98) were exacerbated in cisplatin treatment associated with R715. Picrosirius red staining were used to asses tubulointerstitial fibrosis, and we confirmed that R715 treatment here also exacerbates fibrosis (cis 0, 225+ 0, 025 cis+R715 0, 345+ 0, 042). Conclusion: Here we show that both deletion and blockage of kinin B1 receptor has deleterious effects in renal injury and fibrosis induced by ongoing cisplatin treatment.